Parametric synthesis of the invariant system of car course stability - Aleksandrov, Yevgen; Aleksandrova, Tetiana; Kostianyk, Iryna; Morgun, Yaroslav (Національний технічний університет "Харківський політехнічний інститут", 2023)
The problem of constructing the invariant stabilizer of the ESP (Electronic Stability Program) car course stability system is considered by implementing two control principles by the electronic brake force distribution unit EBD (Electronic Brakeforce Distribution) – the principle of control by deviation and the principle of control by external disturbance. The values of the variable parameters of the stabilization algorithm are selected from the conditions for minimizing both the static and dynamic errors of the system. Two brake fluid pressure sensors are introduced into the EBD structural-functional scheme in the brake lines of the right and left sides of the car. It is proven that the pressure difference of the brake fluid, which is measured by pressure sensors, is proportional to the external disturbance acting on the car body from the side of the road surface. Therefore, in order to give the ESP system the property of invariance to external disturbances, the control signal generated by the EBD electronic unit contains current information not only about the parameters of the disturbed movement of the car, namely, about the angle of deviation of the longitudinal axis of the car relative to the given direction of movement, about the angular velocity of rotation of the body relative to its vertical axis and about lateral displacement of the center of mass of the body, but also the current information about the external disturbance acting on the car body. Recommendations for choosing the values of variable parameters of the ESP system stabilizer are given, which ensure the minimization of both static and dynamic errors of the closed system in the emergency braking mode.

Розглядається задача побудови інваріантного стабілізатора системи курсової стійкості автомобіля ESP (Electronic Stability Program) шляхом реалізації електронним блоком розподілення гальмівних зусиль EBD (Electronic Brakeforce Distribution) двох принципів керування – принципу керування за відхиленням і принципу керування за зовнішнім збуренням. Значення варійованих параметрів алгоритму стабілізації обираються з умов мінімізації як статичної, так і динамічної похибок системи. В структурно-функціональну схему EBD вводяться два датчики тиску гальмівної рідини в гальмівних магістралях правого і лівого бортів автомобіля. Доводиться, що різниця тисків гальмівної рідини, яка вимірюється датчиками тиску, пропорційна зовнішньому збуренню, що діє на корпус автомобіля з боку дорожнього покриття. Тому, для надання системі ESP властивості інваріантності до дії зовнішніх збурень сигнал керування, що формується електронним блоком EBD, містить поточну інформацію не тільки про параметри збуреного руху автомобіля, а саме, про кут відхилення поздовжньої осі автомобіля відносно заданого напрямку руху, кутову швидкість повороту корпусу відносно його вертикальної осі та бічний зсув центру мас корпусу, але й поточну інформацію про зовнішнє збурення, що діє на корпус автомобіля. Додаються рекомендації про вибір значень варійованих параметрів стабілізатора системи ESP, які забезпечують мінімізацію як статичної, так і динамічної похибок замкнутої системи в режимі термінового гальмування.
Параметричний синтез інваріантної системи курсової стійкості автомобіля
Keywords: car course stability system; invariant stabilizer; static error of system; dynamic error of system; variable parameters of stabilizer; система курсової стійкості автомобіля; інваріантний стабілізатор; статична похибка системи; динамічна похибка системи; варійовані параметри стабілізатора